Immunological Regulation of Fibrosis During Heart Failure: It Takes Two to Tango - Vinay Kumar; Shyam S. Bansal (Biomolecules)
Immuno-fibrotic networks and their protein mediators, such as cytokines and chemokines, have increasingly been appreciated for their critical role in cardiac healing and fibrosis during cardiomyopathy. Immune activation, trafficking, and extravasation are tightly regulated to ensure a targeted and effective response against non-self antigens/pathogens while preserving tolerance towards self-antigens and coordinate fibrotic responses for efficient scar formation, a distinction that is severely compromised during chronic diseases. It is clear that immune cells are not only the critical regulators of post-infarct healing and scarring but are also the key players in regulating fibroblast activation during left-ventricular (LV) remodeling. Incomplete resolution coupled with sustained low-grade inflammation during dilated cardiomyopathy precipitates a “frustrated” immune cell response resulting in unconstrained pro-fibrotic and pro-hypertrophic signaling to induce maladaptive structural and functional changes in the myocardium. The aims of this review are to (i) briefly summarize the role of key immune cells that regulate wound healing during MI and fibrosis during LV remodeling; (ii) underscore phenotypic diversities in immune cells and their subsets to underscore their role in regulating fibrotic responses, and, last but not the least, (iii) highlight gaps in our understanding that restrict the translation of immuno-modulatory therapies from the preclinical models to heart failure patients.